EVALUATION OF THE URINARY SODIUM EXCRETION IN PATIENTS WITH LOW SODIUM DIET - Andrea Emanuela; Chaud Hallvass; Lígia Maria Claro; de Moraes; Carlos Thyago; Proença Aita; Roberto Pecoits-Filho (The Korean Society of Nephrology, 2012)
One of the factors involved in the progression of chronic kidney disease (CKD) is the intake of salt. The ratio of salt to hypertension, cardiovascular and cerebrovascular diseases has been extensively demonstrated in several studies. The purpose of this study was to estimate sodium intake in a group of patients with CKD and compared with the urinary excretion of sodium in patients with CKD of any cause at all stages of kidney disease. The design was a cross-sectional observational study, reflecting the initial moment of a protocol of a randomized, prospective and controlled study (Salted). On the same visit was also conducted to collect a food recall. The dietary sodium intake was calculated from the 3-day food record using the Software Avanutri®. For the analysis of sodium added to foods, each 1000mg of salt purchased for the family was divided by the number of people living with the patient, and the result was divided by the number of days that the patient reported the duration of salt until the next purchase. Urinary sodium was measured in urine samples from 24 hours through automated method (CI-8200 Architect - Abbott Diagnostics). After this analysis, we performed a correlation between food records provided by the patient and the result of urinary sodium excretion. Forty-one patients were included, with glomerular filtration rate averaged 38.83 ± 13.63 ml / min. The data correlation between the questionnaire data to assess the sodium intake (food record) show a predominance of intake of sodium added to food. The sodium content of foods was on average 1.31 ± 1.0 g / day and added 5.12 ± 5.8 g / day. The sum of dietary sodium intake and sodium added to food was 6.7 ± 6.93 g / day, showing that 73.17% (n = 30) of patients have a sodium intake above recommended for CKD (4g/day). The urinary sodium measured in the urine of 24 hours was 4.46 ± 1.69 g/24hs. Finally, the correlations between the data from food records and levels of urinary sodium are statistically significant (Pearson correlation coefficient of 0.34 and p 0.03). We conclude that sodium intake in this population at risk is excessive. There was good correlation between the intake of sodium and excretion. Future studies should examine the impact of nutritional interventions aimed at reducing sodium intake in this group of patients.